Effect of Porcine Chondrocyte-Derived Extracellular Membrane (CDECM) on Postoperative Wound Healing in an Experimental Rabbit Model of Glaucoma Filtration Surgery. (3rd June 2017) - Kim, Jung Lim; Lee, Hye Sook; Lee, Yoonjin; Kang, Mi Seon; Lee, Sang Joon; Yang, Jae Wook
ABSTRACT: Purpose : We investigated whether a chondrocyte-derived extracellular membrane (CDECM) could reduce postoperative scar formation in an experimental rabbit model of glaucoma filtration surgery. Methods : Thirty-six male New Zealand white rabbits underwent experimental glaucoma filtration surgeries on the right eye and were randomly divided into the following two treatment groups: the CDECM group was treated with subconjunctival injections of 0.1ml CDECM (25 mg/ml; n = 18 eyes), and the operation (OP) group was treated with subconjunctival injections of 0.1 ml balanced salt solution (n = 18 eyes). The left eyes were used as controls (n = 36 eyes). The effects of the CDECM on the experimental rabbit model were investigated using histopathological, immunochemical analyses and Western blotting analyses of the inflammation, fibrosis and angiogenesis. Results : On the 14th postoperative day, the eyes of the CDECM group displayed reduced vascularity and fibrosis compared with the OP group. The vascular endothelial growth factor (VEGF), CD31 and TNFβ immunostaining were also reduced in the CDECM group. The level of TNFα mRNA was increased in the OP group. On the 28th postoperative day, the eyes of the CDECM group also exhibited reduced vascularity and less inflammation and fibrosis than those of the OP group. The expressions of VEGF, CD31, macrophage, TNFβ and NF-κB p65 were also decreased in the CDECM group. The levels of TNFα mRNA significantly differ, and the level of matrix metallopeptidase 9 (MMP9) was increased in the OP group. To determine the specific upstream pathway that was associated with NF-κB activation due to glaucoma filtration surgery, we measured Akt, PKCs and MAPKs signaling. The phosphorylation of p38 MAPK was increased in the OP group, whereas this expression was decreased by CDECM treatment. Conclusions : CDECM seems to suppress angiogenesis, inflammation and fibrosis, which were related to wound healing in the experimental rabbit model of glaucoma filtration surgery. This effect, resulting from the inhibition of NF-κB expression, may be the blocking of the p38 MAPK signaling pathway.